Los Determinantes Sociales de la Salud: base teórica de la salud pública (2013)
ABSTRACT: This article presents a historical overview of the concept of social determinants of health, in the perspective of the different theoretical and conceptual contributions provided by some academics of health public discipline. For its purpose, first are recognized some of the public health germ concepts and its relationship with social determinants of health and social welfare. Then, it´s looks for the concepts of social determinants into the statements of International Conferences on Health Promotion since Alma Ata. After, synthetically are presented the most recent conceptual contributions since the point of view of the Latin American Movement of Social Medicine, and the more relevant concepts and categories developed from the approach of the Commission on Social Determinants of Health of the World Health Organization. Finally, are addressed a brief discussion and some conclusions.